Early manifestations in a cohort of children prenatally diagnosed with 47,XYY. Role of multidisciplinary counseling for parental guidance and prevention of aggressive behavior - Lalatta, Faustina (BioMed Central, 2012)
BACKGROUND: An increasing number of foetuses are recognized as having double Y because of the widespread use of prenatal screening using chorionic villus sampling and amniocentesis. 47, XYY karyotype occurs in about one out of 1,000 newborn males, but it is not often detected unless it is diagnosed during prenatal testing. Despite the fact that unbiased follow-up studies demonstrate largely normal post-natal development of young men with 47, XYY, there is a scarcity of controlled studies about the neurological, cognitive and behavioural phenotype which remains the main reason for anxiety and anticipatory negative attitudes of parents. Furthermore, prejudices still exist among professionals and the general population concerning the relationship between this sex chromosome aneuploidy and aggressive and antisocial behaviours. METHODS: We report on the clinical follow-up of children diagnosed prenatally with a 47,XYY karyotype, whose parents received multidisciplinary counselling and support at time of diagnosis. The specific focus of our study is on auxology, facial features, developmental milestones, behaviour, detection of aggressiveness as well as the evaluation of parental attitudes toward prenatal counselling. Clinical evaluations including auxological measurements and dysmorphological descriptions were as conducted on 13 boys aged 9 month -7 years. The Child Behavior Check List test specific for age and a 15 item questionnaire were administered to both parents. An update of ongoing problems was carried out by means of a telephone interview two years later. RESULTS: Our results show that, from birth, weight, height and head circumference were above average values while some facial features such mild hypertelorism are overrepresented when compared to parents' facial features. Language delay was detected in 8 out of 11 children older than 20 months. Parental attitudes were found to be favourable toward prenatal diagnoses of sexual chromosome aneuploidies. CONCLUSIONS: Our data, although limited, is similar to other observational studies, and serves to alert clinicians about opportunities to delineate new and appropriate educational interventions that target the specific learning challenges of XYY boys. Our experience better defines the early manifestation of XYY and should aid those involved in prenatal counselling and paediatric surveillance.